Umrah Service Management PT. Zakiah Dina Tayyibah - Muhammad Majdy Amiruddin; Najamiah Amir; Rezky Meilia Sari (Tadbir: Jurnal Manajemen Dakwah, 2020)
This research is to analyze the strategy of umrah pilgrimage services in PT. Zakiah Dina Tayyibah. This research uses descriptive mothod. The data collection techniques obtained through interviews, observation, and documentation. This research shows that PT. Zakiah Dina Tayyibah can improve services and strengthen a company. PT. Zakiah Dina Tayyibah uses several strategies with brochures, websites, and others so as to improve the quality of the company’s services PT. Zakiah Dina Tayyibah also provides several branch companies in various regions making it easier for pilgrims to access information and to register umrah pilgrims